1996
DOI: 10.1097/00005344-199606000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Effect Study of Beraprost Sodium in Intermittent Claudication

Abstract: We compared the efficacy and safety of three doses of beraprost sodium, an epoprostenol analogue, with placebo in the treatment of intermittent claudication (Fontaine's stage II). One hundred sixty-four patients were randomized to receive either placebo, 20 micrograms beraprost sodium (BPS60 group), 40 micrograms beraprost sodium (BPS120 group), or 60 micrograms beraprost sodium (BPS180 group) three times daily administered orally in a double-blind manner for 12 weeks. Treadmill exercise tests were performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The absence of any effect of the treatment on the ABI before treadmill exercise and on the loss in this index during exercise could be anticipated from the results of the BERCI dose-effect study 9 and are in accordance with the results of most clinical trials in intermittent claudication. 11,19,20 In 1 study of cilostazol, however, the increase in walking distance was accompanied by a small but significant increase in the ABI compared with placebo.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The absence of any effect of the treatment on the ABI before treadmill exercise and on the loss in this index during exercise could be anticipated from the results of the BERCI dose-effect study 9 and are in accordance with the results of most clinical trials in intermittent claudication. 11,19,20 In 1 study of cilostazol, however, the increase in walking distance was accompanied by a small but significant increase in the ABI compared with placebo.…”
Section: Discussionsupporting
confidence: 77%
“…7 We assessed the effects of BPS on walking distances in patients with intermittent claudication in the Beraprost et Claudication Intermittente (BERCI) dose-effect study. 9 In this 12-week study, BPS increased the pain-free walking distance, compared with placebo, at doses of 20 and 40 g TID but not at This trial was financed by an unrestricted grant from Laboratories Hoechst Houde (France). Drs Lievre and Boissel received an institutional grant from Laboratories Hoechst Houde for data management and analysis of the BERCI-2 study.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…11 The treadmill protocol used to assess the primary study endpoint was the G-test. The study protocol was approved by the institutional review boards of the centers involved; each patient signed a written consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Placebo-induced improvements in walking distance of more than 40% over baseline have been observed in several trials. [23][24][25] In another study a steady progressive improvement in claudication distance was reported for placebo increasing by 28% over 12 months. 15 This remarkable placebo effect is generally attributed to an improved exercise capacity from repeated examinations -a training effect.…”
Section: Discussionmentioning
confidence: 93%